Hubungan Kemampuan Mengajar Guru dan Minat Belajar Siswa Terhadap Hasil Belajar Bahasa Arab Di MTsN 1 Palembang - Nazarmanto Nazarmanto; Suryati Suryati (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
ENGLISH:The research aims to explain the correlation of teachers' teaching abilities to student learning outcomes, student learning interests to learning outcomes and the combination of the two. Respondent was one Arabic teacher at MTS Negeri 1 Palembang and 35 students. Quantitative research methods using regression analysis techniques assisted by the SPSS program. The findings obtained are that the teaching ability possessed by the teacher influences the results of the students by 3.1%. It was also found that the results of the student learning interest factor on student learning outcomes were 30.6%, while the combination of the two, namely the ability of the teacher to teach and the interest of the students, was 34.7%. Based on these data it can be seen that the ability of the teacher to teach and students' interest in learning is stated to have an effect on the student's learning outcomes.INDONESIA:Penelitian bertujuan menjelaskan korelasi kemampuan mengajar guru terhadap hasil belajar siswa, minat belajar siswa terhadap hasil belajar dan kombinasi dari keduanya. Responden satu guru bahasa Arab MTS Negeri 1 Palembang dan 35 siswa-siswi. Metode penelitian kuantitatif dengan menggunakan teknik analisis regresi berbantuan program SPSS. Temuan yang didapatkan yaitu kemampuan mengajar yang dimiliki oleh guru mempengaruhi hasil dari siswa sebanyak 3,1%. didapatkan juga hasil dari faktor minat belajar siswa terhadap hasil belajar siswa sebesar 30,6% sedangkan kombinasi dari keduanya yaitu dari kemampuan guru mengajar dan minat dari peserta didik yaitu 34,7%. Berdasarkan data tersebut dapat diketahui bahwa kemampuan dari mengajar guru dan minat siswa pada pembelajaran dinyatakan berpengaruh terhadap hasil belajar siswa tersebut.